Assessment of Patients for Treatment with Tinnitus Retraining Therapy - Henry, James A.; Jastreboff, Margaret M.; Jastreboff, Pawel J.; Schechter, Martin A.; Fausti, Stephen A. (Journal of the American Academy of Audiology, 2002)
Clinical management for patients complaining of severe tinnitus has improved dramatically in the last 25 years. During that period of time, various methods of treatment have been introduced and are being used with varying degrees of success. One method that has received considerable attention is tinnitus retraining therapy (TRT). This method is being practiced by hundreds of clinicians worldwide, and retrospective clinical data indicate that TRT has been effective for the majority of patients. This article provides a guide for clinicians to evaluate their patients for treatment with TRT. Included in this guide is the expanded version of the TRT initial interview and specific instructions for the clinician administering the interview.
Keywords: hearing disorders; tinnitus